Implementing Accounting Information Systems for Financial Transparency and Accountability in Zakat Institutions - Putri Dewintari; Abid Ramadhan; Rahmat Siswanto (www.amertainstitute.com, 2024)
This research aims to develop and implement a PSAK 109-based Accounting Information System (AIS) using the e-FAMS application to improve transparency and accountability in the financial management of zakat institutions. e-FAMS is designed using the waterfall method, which includes the stages of needs analysis, system design, implementation, testing, and maintenance. The implementation results show that e-FAMS supports real-time and accurate recording and reporting of zakat, infaq, and sadaqah transactions in accordance with PSAK 109 standards, which improves efficiency and reduces manual errors in reporting. With web-based features, the application allows flexible accessibility for management and provides high data security, thus strengthening public trust in zakat institutions. Digitalization through e-FAMS also simplifies the audit and reporting process, accelerating access to financial information needed by external parties. In conclusion, the implementation of e-FAMS provides an effective solution for zakat institutions in meeting applicable accounting standards and responding to public demands for professional and accountable financial management.